2005
DOI: 10.1227/01.neu.0000176709.19954.eb
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Osseous Hemangioblastoma of the Thoracic Spine: Technical Case Report

Abstract: Although extremely rare, hemangioblastomas may occur in a purely osseous location. They may resemble vertebral hemangioma. Treatment should include aggressive surgical removal, although arduous, if appropriate. A bilateral lateral extracavitary approach is ideal for complete spondylectomy. With this technique, ventral and dorsal reconstruction of the spine through the same incision is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Freidman (10) suggested that aggressive hemangioma should be considered with the following characteristics: female patient, marked hyperintensity on T2, intrasseous signal voids or mottled appearance, midthoracic location, and enlarged paraspinal vessels. Differential diagnoses would include osseous tumor such as Ewing sarcoma (11) or Hemangioblastoma (12).…”
Section: Discussionmentioning
confidence: 99%
“…Freidman (10) suggested that aggressive hemangioma should be considered with the following characteristics: female patient, marked hyperintensity on T2, intrasseous signal voids or mottled appearance, midthoracic location, and enlarged paraspinal vessels. Differential diagnoses would include osseous tumor such as Ewing sarcoma (11) or Hemangioblastoma (12).…”
Section: Discussionmentioning
confidence: 99%